Employee Data Information System in Peukan Baro District, Pidie Regency - Muammar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research explores the creation and implementation of an Employee Data Information System (EDIS) in Peukan Baro District, Pidie Regency, designed to replace the outdated manual system used for managing employee data. The previous system, which relied on Microsoft Word and Excel, was inefficient, especially in tasks such as searching for employee data and generating reports. To address these challenges, a new system was developed using Microsoft Visual BASIC 6.0 and Microsoft Access 2007. The system streamlines the data management process, enabling real-time updates and enhancing the decision-making process. The development followed a series of steps, including a Feasibility Study, Preliminary Planning, System Analysis, and System Design, where the needs of the users were gathered through interviews, observations, and document analysis. The system design incorporates user-friendly forms such as the Employee Data Input and Training Data Input forms, allowing for smooth data entry and reducing the risk of errors. The Main Menu Form functions as a central navigation point, giving users easy access to various sections of the system. The implementation of EDIS improved the quality of public services in the district by making employee data more accessible and streamlining administrative tasks. The findings suggest that the success of such a system relies on more than just technology. Infrastructure readiness, employee training, and leadership support play critical roles in ensuring the effective use of digital systems in public administration.